Expression of frutalin, an α-d-galactose-binding jacalin-related lectin, in the yeast Pichia pastoris - Oliveira, Carla Cristina Marques de (2008)
Frutalin is an α-d-galactose-binding lectin expressed in breadfruit seeds. Its isolation from plant is time-consuming and results in a heterogeneous mixture of different lectin isoforms. In order to improve and facilitate the availability of the breadfruit lectin, we cloned an optimised codifying frutalin mature sequence into the pPICZαA expression vector. This expression vector, designed for protein expression in the methylotrophic yeast Pichia pastoris, contains the Saccharomyces α-factor preprosequence to direct recombinant proteins into the secretory pathway. Soluble recombinant frutalin was detected in the culture supernatants and recognised by native frutalin antibody. Approximately 18–20 mg of recombinant lectin per litre medium was obtained from a typical small scale methanol-induced culture purified by size-exclusion chromatography. SDS–PAGE and Edman degradation analysis revealed that frutalin was expressed as a single chain protein since the four amino-acid linker peptide “T-S-S-N”, which connects α and β chains, was not cleaved. In addition, incomplete processing of the signal sequence resulted in recombinant frutalin with one Glu-Ala N-terminal repeat derived from the α-factor prosequence. Endoglycosidase treatment and SDS–PAGE analysis revealed that the recombinant frutalin was partly N-glycosylated. Further characterisation of the recombinant lectin revealed that it specifically binds to the monosaccharide Me-α-galactose presenting, nevertheless, lesser affinity than the native frutalin. Recombinant frutalin eluted from a size-exclusion chromatography column with a molecular mass of about 62–64 kDa, suggesting a tetrameric structure, however it did not agglutinate rabbit erythrocytes as native frutalin does. This work shows that the galactose-binding jacalin-related lectins four amino-acid linker peptide “T-S-S-N” does not undergo any proteolytic cleavage in the yeast P. pastoris and also that linker cleavage might not be essential for lectin sugar specificity.